The adverse events of toripalimab in nasopharyngeal carcinoma based on FAERS database and bibliometric analysis. - Qian Guo; Dong Dong; Zihan Dang; Shuman Huang; Xinjie Qiao; Baiquan Zhang; Yulin Zhao (PLoS ONE)
Background Toripalimab, a monoclonal antibody designed to target PD-1, has recently received approval from the U.S. Food and Drug Administration (FDA) for use as a first-line treatment in adults diagnosed with metastatic or recurrent locally advanced nasopharyngeal carcinoma (NPC). The purpose of this study is to utilize the FAERS database and bibliometric analysis to examine adverse events associated with toripalimab in real-world settings, thereby enhancing the safety management of clinical medications. Methods This research implemented a disproportionality analysis to assess the safety of toripalimab by reviewing all adverse event reports from the FAERS database dating back to 2004, wherein toripalimab was recognized as the main suspected medication. Various statistical techniques were applied in the analysis, such as the reporting odds ratio (ROR), proportional reporting ratio (PRR), multi-item gamma Poisson shrinker (MGPS), and Bayesian confidence propagation neural network (BCPNN), to evaluate the adverse events linked to toripalimab. CiteSpace is utilized to search for authors, countries, keywords, and various indicators within research fields, facilitating the identification of research hotspots and future trends. Results From 2004 to 2024, 441 AEs linked to toripalimab were recorded across 27 SOCs. The top five SOCs were procedural complications, investigations, blood/lymphatic disorders, gastrointestinal disorders, and skin/subcutaneous disorders. At the PT level, the top five AEs by ROR were myelosuppression (n = 192, ROR 687.41), decreased granulocyte count (n = 11, ROR 515.72), immune-mediated hepatic disorder (n = 7, ROR 343.20), immune-mediated myocarditis (n = 3, ROR 214.68), and bicytopenia (n = 3, ROR 117.49). Additionally, 91.62% of AEs occurred within the first 30 days, and immune-related AEs were highlighted in bibliometric analysis. Conclusion This research provides initial safety information regarding the real-world application of toripalimab, affirming previously acknowledged adverse effects and concurrently uncovering new possible risks. These results could act as important cautionary evidence for healthcare professionals and pharmacists engaged in administering toripalimab for NPC.